Professional Development of Public Secondary School Administrators: Basis for Lifelong Learning Framework - Baldovino, C M V (KnE Social Sciences, 2018)
There is a need for school administrators of today to adapt to the current radical changes in the educational system. This includes the application of lifelong learning as stated in the United Nation’s sustainable development goals. For this reason, this study sought to develop a lifelong learning framework that will help enhance the professional development of school administrators. Data were gathered and processed using quantitative and qualitative approaches. The findings revealed that only limited formal lifelong learning activities were attended by public secondary school administrators in the Division of Quezon due to the following emerging barriers: money, time, age, fear and necessity. The respondents’ knowledge of, skills in and attitudes towards lifelong learning are deemed to be strong; however, results have shown that they have less knowledge compared to their skills and attitude. Eagerness is a stimulating factor which is vital in order to involve in the process of learning. Thus, results from this study showed that time, energy, confidence and self-motivation are some existing needs perceived by the respondents. Moreover, it also suggests that the administrators must be equipped with proper and ample knowledge of lifelong learning concepts since unconsciously they are already actively engaging themselves in it through their different daily activities. Furthermore, it is essential to create a specialized framework that will aid them to pursue continuous progress throughout their profession. Hence, a lifelong learning framework for the professional development of public secondary school administrators was proposed and served as the primary outcome of this study. Keywords: framework, lifelong learning, professional development, school administrators